Síntese, caracterização e verificação da viabilidade físico-química e celular dos compostos de Ru (III) [Ru(bipy)(Cl)₃(H₂O)] e [Ru(bipy)(Cl)₃(4-ampy)].2H₂O - Dantas, Rans Miler Pereira (2024)
Coordination compounds are made up of metal atoms or ions linked to other atoms or molecules called ligands. N-heterocyclic ligands have one or more aromatic rings in their structure and also have some nitrogen atom in addition to, of course, carbon atoms. The bipy ligand is able to bind strongly to the metal center with efficiency and stability. The 4-ampy compound is one of the compounds used to treat multiple sclerosis, an autoimmune disease. Due to Ru's ability to imitate the binding of iron with biomolecules, compounds with this transition metal have been used as a potential antitumor agent. The present work aims to synthesize, characterize and evaluate the physicochemical and cellular viability in peripheral blood mononuclear cells (PBMC) of two Ru coordination compounds in the oxidation state (III), using RuCl₃.xH₂O with the ligand bipy and later with the 4-ampy ligand. It was possible to determine their properties through analysis in the infrared region, TG/DTG and DSC for both compounds. It was also possible to verify the solubility of the compounds where it was noted that the compound [Ru(bipy)(Cl)₃(H₂O)] is poorly soluble and the modified compound [Ru(bipy)(Cl)₃(4 ampy)].2H₂O is more soluble following the method described by the Brazilian pharmacopoeia. Its physical-chemical properties were verified through the partition coefficient (logP) that the modified compound is more soluble than its precursor. Finally, biological cell viability assays statistically showed that the compounds studied did not present cytotoxicity in PBMC cells and, as future work, the compounds will be tested in MCF-7 cells.